Education Practices Mediated by Digital Technologies: Mobilization and Teachers' Strategies in Primary and Secondary Schools in Germany - Eucidio Pimenta Arruda; Michael Kerres (MDPI AG, 2024)
This article presents the results of the research "post-pandemic education: understanding of analogic education and digital education from the perspective of educational institutions and teachers in Brazil and Germany", whose main objective is to analyze how teachers and educational institutions mobilize and position themselves for the expansion of digital education practices. The following methods were used: documentary research with the German state secretariats of education, as well as documentary analysis of educational policies aimed at the implementation of digital information and communication technologies in compulsory education in Germany. We then proceeded to construct a large-scale survey to be answered by teachers of distinct levels of education. We contacted around 9400 compulsory education institutions in the three largest German states in terms of population. As a result, in general, teachers understand the importance of digital technologies in student education and demonstrate knowledge of the policies established by public agencies of the state. The mobilizations around digital pedagogical practices reveal the importance of considering teachers' and students' knowledge about technologies inside and outside the school context. The results allow us to understand the place that digital technologies occupy in the daily teaching routine.